In Situ Focused Beam Reflectance Measurement (FBRM), Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) and Raman Characterization of the Polymorphic Transformation of Carbamazepine - Sohrab Rohani; Yingying Zhao; Ying Bao; Jingkang Wang (MDPI AG, 2012)
The objective of this work was to study the polymorphic transformation of carbamazepine from Form II to Form III in 1-propanol during seeded isothermal batch crystallization. First, the pure Form II and Form III were obtained and characterized. Then their solubilities and metastable zone limits were measured by in-situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and focused beam reflectance measurement (FBRM). A transition temperature at about 34.2 °C was deduced suggesting the enantiotropic nature of this compound over the studied temperature range. To quantify the polymorph ratio during the transformation process, a new in-situ quantitative method was developed to measure the fraction of Form II by Raman spectroscopy. Successful tracking of the nucleation of the stable form and the transformation from Form II to Form III during isothermal crystallization was achieved by Raman spectroscopy and FBRM. The results from these three in-situ techniques, FBRM, FTIR and Raman were consistent with each other. The results showed a strong dependency on the amount of seeds added during isothermal crystallization.